Genetic Diversity and Demographic Connectivity of Atlantic Green Sea Turtles at Foraging Grounds in Northeastern Colombia, Caribbean Sea - Vásquez-Carrillo, Catalina; Noriega-Hoyos, Carmen L.; Hernandez-Rivera, Leidy; Jáuregui-Romero, Guiomar Aminta; Sullivan Sealey, Kathleen (Frontiers in Marine Science, 2020)
The Atlantic green sea turtle Chelonia mydas is a migratory and endangered species with a network of nesting rookeries and foraging grounds in the Atlantic basin that needs elucidation. Foraging grounds are important areas for immature turtle’s feeding and growth after pelagic migrations. Aggregations of sea turtles at these grounds usually come from genetically distinct nesting rookeries; therefore, they are called mixed stocks. The northeastern coast of Colombia has extensive seagrass and macroalgae marine ecosystems that constitute foraging grounds, and perhaps long-term developmental habitats for a significant number of immature C. mydas. However, it is unknown which C. mydas nesting rookeries may be using these ecosystems for feeding and development. This study estimated the genetic diversity and genetic origin of C. mydas mixed stocks at two foraging grounds in northeastern Colombia (Santa Marta and La Guajira), and inferred their connections to nesting rookeries groups in the Atlantic basin using mitochondrial Control Region (mtCR) as a marker. A high genetic diversity, evidenced by the high nucleotide and haplotype diversities, was found in both studied mixed stocks and may be explained by different contributing nesting rookeries groups found with mixed stock analyses. At least three genetically distinct groups from different sides of the Atlantic Basin contributed juveniles to the mixed stocks in Colombia. Observed demographic connectivity can be explained by the confluence of two major, opposite directions ocean currents by the study area, the Caribbean Current (westward) and the Panama-Colombia Countercurrent (eastward). The high diversity of turtles at Colombia’s foraging grounds suggests the area is an important link in the network of habitats used by C. mydas to be considered in management and transnational conservation planning for the species recovery.